Driving Forces, Barriers and Competences in The Implementation of Industry 4.0: Literature Review - Anna MICHNA; Joanna KRUSZEWSKA (Communications of International Proceedings, 2021)
The aim of this article is to present summary of performed literature review in the area of driving forces, which lead companies to implement the solutions of Industry 4.0, barriers and limitations that may delay or completely eliminate the possibility of digitizing small and medium-sized enterprises, as well as competences necessary for successful implementation of I4.0, taking into account the level of employees, specialists and managers. It also discusses the competences and skills, in case of which the current situation undergoes significant transformation, requires adaptation or complete change. As a practical aspect of the presented research, all models and outcomes will be used for next planned empirical study, based on anonymous survey, planned for the second half of the current year for SMEs in the Polish automotive market.
Keywords: Industry 4.0; Solutions; Barriers; Chances; Driving Forces; Competences.